2017
DOI: 10.3897/neobiota.34.10820
|View full text |Cite
|
Sign up to set email alerts
|

Biotic constraints on the establishment and performance of native, naturalized, and invasive plants in Pacific Northwest (USA) steppe and forest

Abstract: Factors that cause differential establishment among naturalized, invasive, and native species are inadequately documented, much less often quantified among different communities. We evaluated the effects of seed addition and disturbance (i.e., understory canopy removal) on the establishment and seedling biomass among two naturalized, two invasive, and two native species (1 forb, 1 grass in each group) within steppe and low elevation forest communities in eastern Washington, USA. Establishment within each plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…in undisturbed than in disturbed plots (Wallace and Prather, 2016). This result is similar to the seed-addition experiment of Connolly et al (2017), who showed that two European invasive species were able to establish in plots without disturbance and did not benefit more from disturbance than native species, even with a standardized amount of added seeds (predictions d) and e)).…”
Section: Are Native Populations With Local Preadaptations To Anthropo...supporting
confidence: 84%
See 1 more Smart Citation
“…in undisturbed than in disturbed plots (Wallace and Prather, 2016). This result is similar to the seed-addition experiment of Connolly et al (2017), who showed that two European invasive species were able to establish in plots without disturbance and did not benefit more from disturbance than native species, even with a standardized amount of added seeds (predictions d) and e)).…”
Section: Are Native Populations With Local Preadaptations To Anthropo...supporting
confidence: 84%
“…Prediction c) has been tested with several large-scale multi-species experiments, which provided mixed support. Researchers studied the response of European invaders to different disturbance regimes such as biomass removal, nutrient addition and soil disruption, and they found no (Connolly et al, 2017;Broadbent et al, 2020;Bellini et al, 2022) or only partial (Maron et al, 2014) support for this prediction. With regard to prediction d), two multispecies experiments that focused on plant responses to soil disruption indeed found that some European species were unable to establish in undisturbed soil (Jesson et al, 2000;Pearson et al, 2022).…”
Section: Are Native Populations With Local Preadaptations To Anthropo...mentioning
confidence: 99%
“…Particularly, new experiments using various biomass treatments have substantially added to our understanding of restoration success. For example, a recent study demonstrated how seed limitation and intact plant ground cover can limit the abundance and performance of naturalized species in Pacific Northwest steppe and low-elevation forests (Connolly et al 2017).…”
Section: Introductionmentioning
confidence: 99%